Geological and Geophysical Studies of the Double Transform Fault Charlie Gibbs (North Atlantic) during Cruise 50 of R/V Akademik Nikolaj Strakhov - Skolotnev, SG; Peyve, AA; Sanfilippo, A; Sokolov, SY; Petracchini, L; Dobrolyubova, KO; Nestola, Y; Ivanenko, AN; Basch, V; Pertsev, AN; Sani, C; Brusilovskiy, YV; et al. (Oceanology, 2022)
This paper provides information on the geological and geophysical studies of the structure of the Charlie Gibbs megatransform system in the North Atlantic on cruise 50 of R/V Akademik Nikolaj Strakhov in September-October 2020. The preliminary results of the expedition are discussed.